2014
DOI: 10.1051/0004-6361/201323016
|View full text |Cite
|
Sign up to set email alerts
|

New constraints on the formation and settling of dust in the atmospheres of young M and L dwarfs

Abstract: Context. Gravity modifies the spectral features of young brown dwarfs (BDs). A proper characterization of these objects is crucial for the identification of the least massive and latest-type objects in star-forming regions, and to explain the origin(s) of the peculiar spectrophotometric properties of young directly imaged extrasolar planets and BD companions. Aims. We obtained medium-resolution (R ∼ 1500−1700) near-infrared (1.1−2.5 µm) spectra of seven young M9.5-L3 dwarfs classified at optical wavelengths. W… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
54
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 51 publications
(62 citation statements)
references
References 146 publications
(260 reference statements)
7
54
1
Order By: Relevance
“…(2014) using the SED only and/or different atmospheric models. The T eff is also coherent with those derived for young objects at similar spectral types Manjavacas et al 2014). The dilution factors needed to adjust the model SED expressed in surface fluxes to the apparent fluxes of the planet correspond to a planetary radius of 1.5 ± 0.2 R Jup (see Bonnefoy et al 2013).…”
Section: Physical Properties and Initial Conditionssupporting
confidence: 76%
See 2 more Smart Citations
“…(2014) using the SED only and/or different atmospheric models. The T eff is also coherent with those derived for young objects at similar spectral types Manjavacas et al 2014). The dilution factors needed to adjust the model SED expressed in surface fluxes to the apparent fluxes of the planet correspond to a planetary radius of 1.5 ± 0.2 R Jup (see Bonnefoy et al 2013).…”
Section: Physical Properties and Initial Conditionssupporting
confidence: 76%
“…We compared the normalized spectrum of β Pic b with predictions from the PHOENIX-based (BT-SETTL10, BT-SETTL13, DRIFT-PHOENIX, described in Witte et al 2011;Bonnefoy et al 2013;Manjavacas et al 2014) and five grids of LESIA atmospheric models (see Appendix C and Baudino et al 2014) to derive updated T eff and log g estimates (Table 2). A similar analysis derived for the up-to-date SED is reported in Appendix D. The SED and spectra of β Pic b constrain the T eff to 1650 ± 150 K. The fits are less sensitive to log g and to the metallicity.…”
Section: Physical Properties and Initial Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…14), we did not find any significant, unambiguous spectral features of a (nonirradiated) low-mass dwarf star (e.g., Li et al 2014;Littlefair et al 2014;Manjavacas et al 2014). In this phase, the expected secondary's contribution to the composite spectrum of AA Dor is of the order of 0.1% in the NIR.…”
Section: Spectrum Of the Secondarymentioning
confidence: 61%
“…In addition, the models do not provide a good fit of the datapoints in the 3−4 µm regime while they are the only ones that account for non-equilibrium chemistry. Manjavacas et al (2014) suggested that the BT-SETTL models do not seem to produce naturally enough dust, especially at high altitude in the cloud. The problem could be emphasized here with the HR8799 planets.…”
Section: Resultsmentioning
confidence: 99%